Ascender. Volume three, The digital mage - Lemire, Jeff (Ascender, 2020)
"Captain Telsa is doing her best to shake off young Mila and Bandit but things gets harder once an old friend wants to tag along - DRILLER, the KILLER ROBOT! With his faithful companion Mizard the Wizard at his side, Mother and her evil army of vamps may have finally met their match. Meanwhile, Andy struggles to resurrect his lost love Effie from the relentless grasp of the vampire undead."--Provided by publisher.